68Ga-DOTATATE and 18F-FDG PET/CT in Paraganglioma and Pheochromocytoma: utility, patterns and heterogeneity. Issue 1 (December 2016) - Chang, Chian; Pattison, David; Tothill, Richard; Kong, Grace; Akhurst, Tim; Hicks, Rodney; Hofman, Michael
Abstract Background Pheochromocytomas (PCC) and paragangliomas (PGL) are neuroendocrine tumours arising from pluripotent neural crest stem cells and are associated with neurons of the autonomic nervous system. PCCs/PGLs are often hereditary and multifocal, and their biologic behaviour and metabolic activity vary making imaging of these tumours challenging. The imaging gold standard has been I-123 MIBG complemented by CT or MRI. PGLs being neuroendocrine tumours express somatostatin receptors enabling imaging with Ga-68 DOTA-coupled peptides such as DOTATATE. Imaging with F-18 FDG also provides additional information regarding metabolic activity and biologic aggressiveness of these tumours, or, in some situations, reflecting metabolic reprogramming of these tumours. We report our experience using both Ga-68 DOTATATE and F-18 FDG PET/CT imaging in patients with PGLs and PCCs. Methods This was a retrospective review of 23 patients with proven PGL/PCC who underwent both DOTATATE and FDG PET/CT. Seven patients also had I-123 MIBG SPECT/CT and 1 patient had I-124 MIBG PET/CT. Lesional intensity and patterns of uptake were analysed. Results DOTATATE and FDG were positive at most sites of disease (96.2 % vs 91.4 %), although uptake intensity was significantly higher on DOTATATE with a median SUV of 21 compared to 12.5 for FDG (p < 0.001). SUVmax on F-18 FDG was significantly higher (p < 0.001) in clinically aggressive cases. I-123/I-124 MIBG detected fewer lesions (30.4 %). Conclusion Overall, Ga-68 DOTATATE PET/CT detected similar number but has significantly greater lesion-to-background contrast compared to F-18 FDG PET/CT. Combined with high specificity, patient convenience and relatively low cost, DOTATATE PET/CT should be considered the ideal first line investigation for imaging PGL/PCC. Depending on DOTATATE findings and the clinical question, FDG and MIBG remain useful and, in selected cases, may provide more accurate staging, disease characterisation and guide treatment choices.